2021
DOI: 10.1186/s13054-021-03502-y
|View full text |Cite
|
Sign up to set email alerts
|

Helmet CPAP to treat hypoxic pneumonia outside the ICU: an observational study during the COVID-19 outbreak

Abstract: Background Respiratory failure due to COVID-19 pneumonia is associated with high mortality and may overwhelm health care systems, due to the surge of patients requiring advanced respiratory support. Shortage of intensive care unit (ICU) beds required many patients to be treated outside the ICU despite severe gas exchange impairment. Helmet is an effective interface to provide continuous positive airway pressure (CPAP) noninvasively. We report data about the usefulness of helmet CPAP during pand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 32 publications
10
57
0
12
Order By: Relevance
“…Several studies have shown improved outcomes with prone positioning ( 37 ) and use of noninvasive ventilatory support in lieu of invasive mechanical ventilation ( 11 , 15 , 38 ) for patients with acute respiratory failure associated with COVID-19. Decreasing use of invasive mechanical ventilation may have also lessened the need for ICU-level care because other types of respiratory support could be delivered in non-ICU settings ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown improved outcomes with prone positioning ( 37 ) and use of noninvasive ventilatory support in lieu of invasive mechanical ventilation ( 11 , 15 , 38 ) for patients with acute respiratory failure associated with COVID-19. Decreasing use of invasive mechanical ventilation may have also lessened the need for ICU-level care because other types of respiratory support could be delivered in non-ICU settings ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“… 107 Helmet CPAP treatment presents a success rate greater than 60% 108 and has been considered as a rescue therapy to improve survival. 109 One RCT is ongoing to evaluate the impact of helmet CPAP in COVID-19 pneumonia patients. 110 …”
Section: How Can P-sili Be Prevented?mentioning
confidence: 99%
“…In other words, as shown in Fig. 2 , positive pressure not only improved oxygenation but also allowed better stratification of patient severity [ 40 ]. Some authors also suggested that an incremental PEEP trial might allow a PEEP selection with optimized oxygenation while avoiding haemodynamic complications [ 41 ].…”
Section: Use Of Helmets To Deliver Cpapmentioning
confidence: 99%
“…The oxygenation increase was more pronounced in patients who could be successfully treated with helmet CPAP without escalation to intubation (white boxes, P = 0.002 for interaction between the CPAP effect and outcome). Reproduced under Creative Common licence from [ 40 ] …”
Section: Use Of Helmets To Deliver Cpapmentioning
confidence: 99%